Association between socioeconomic positions and overweight/obesity in rural Nepal - Bhattarai, Sanju; Nerhus Larsen, Rikke; Shrestha, Archana; Karmacharya, Biraj; Sen, Abhijit (Frontiers in Nutrition, 2022)
Introduction: Obesity and its association with socioeconomic factors are well established. However, the gradient of this relationship among rural populations in low- and middle-income countries like Nepal are not fully understood. We sought to assess the association of socioeconomic factors (education, income, and employment status) in relation to overweight/obesity. Methods: This cross-sectional study analyzed data from 260 participants aged ≥18 years attending a rural health center in Dolakha, Nepal. Self-reported data on demographic, socioeconomic, and lifestyle factors was collected, and weight, and height were measured for all study participants. Those with body mass index of <25 kg/m2 were regarded as non-overweight/obese and ≥ 25.0 kg/m2 as overweight/obese. Poisson regression models were used to estimate the prevalence ratios and corresponding 95% confidence intervals to assess the association between socioeconomic factors and overweight/obesity. In addition, we assessed effect-modification by age and gender to study the effect of socioeconomic factors on overweight/obesity. Results: The age standardized prevalence of overweight/obesity was higher for individuals with higher education (23%), high-income (32%) and unemployed (42%). Compared to low-income and no formal education group, the prevalence ratio of overweight/ obesity was 1.69 and 2.27 times more for those belonging to the high-income and high school and above, respectively. No evidence of effect modification by gender and age was observed. Conclusions: Socioeconomic factors, education and income were positively associated with overweight/ obesity prevalence in rural Nepal. Further, large studies using longitudinal settings are necessary to replicate our findings.